Success factors for bumiputra contractors in Malaysia : Johor state - Rahmat, Noor Idirah (2016)
Several parties which include client, consultant, contractor, supplier and local authorities are involved in ensuring the success of a construction project. Among these parties, contractor plays the most important role in making the project success within stipulated time, cost and quality. In reality, studies reported that construction projects often encountered delays or late deliveries, sub-standard workmanship and materials, poor safety management on sites and cost over-run of construction due to problems encountered by contractors in executing the project. Since many of these studies uncovered the contractors’ problems, thus this study was intended to determine success factors for contractors focusing on Bumiputra contractors. This is a quantitative study where data was collected using questionnaire survey and analysed using descriptive and multivariate approach. Pilot study was carried out to assess contents validity of the questionnaire on the 33 identified success factors by 10 experienced Bumiputra contractors. After the pilot study, actual survey managed to secure responses of 100 Bumiputra contractors for the state of Johor. Descriptive analysis on the collected data has resulted to five most significant success factors for Bumiputra contractors which are prepare competitive tender pricing for tendering process, maintain good reputation for better chance of getting new project, filling correct terms and condition in tender document, manage risk of not having good and sustainable team of construction workers and manage workers to carry out the given tasks in systematic manner. PLS-SEM path modelling approach was used to develop a model showing the graphical relationships of the success factors. Based on the developed model, it was found that factors in resources group are giving the highest impact load of 0.299 to the success of Bumiputra contractors. Hopefully, the findings from this study will be a constructive guide to Bumiputra contractors to improve their potentials to be successful in the competitive construction business.